An Analysis of Muzakis Behavior in Paying Zakat Mal and Factors Influencing It: The Perspective of The Theory of Planned Behavior - Santoso, Slamet; Cahyono, Yeni; Wafirotin, Khusnatul Zulva; Ayutika, Riza Dessy Nila (IAIN Surakarta, 2021)
This study seeks to explore factors influencing the behavior of muzaki in paying zakat mal by applying the Theory of Planned Behavior. Referring to Theory of Planned Behavior, attitudes, subjective norms, behavioral controls, and intention influence the behavior of muzaki in paying zakat mal. This study was carried out to permanent muzaki registered at the legal Amil Zakat Institutions in Ponorogo Regency. This quantitative study used primary data in the form of questionnaires. The population in this study is permanent muzaki registered at the Amil Zakat Institutions in Ponorogo Regency such as LazisMu, Yatim Mandiri, and LAZ Baitul Maal Hidayatullah. Involving 80 respondents, the sampling technique used was saturation sampling, in which all members of the population are taken. Performing the SmartPLS 3.0, data analysis includes the Measurement Model (Outer Model) and Structural Model (Inner Model). The results show that the variable of Attitude and Behavioral Control have a positive and significant influence on the intention of muzaki in paying zakat mal, while the variable of Subjective Norms did not affect the intention of muzaki paying zakat mal. The variable of Intention shows a significant influence on the behavior of muzaki paying zakat mal. Keywords: Zakat Attitude, Subjective Norm, Perceived Behavioral Control